1979
DOI: 10.1007/bf01235858
|View full text |Cite
|
Sign up to set email alerts
|

Insulin production rate following glucose ingestion estimated by splanchnic C-peptide output in normal man

Abstract: Insulin production rate has been estimated in healthy male volunteers (n = 16), and evaluated with respect to splanchnic glucose exchange. Insulin production rate was calculated from splanchnic immunoreactive C-peptide output. C-peptide secretion was estimated by the hepatic venous catheter technique both in the basal state and for 2 h following ingestion of various glucose loads (0, 12.5, 25, 50, 75, and 100 g). The results demonstrate a basal insulin production rate of 0.017 +/- 0.002 U/min (mean +/- SEM) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
88
1
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(95 citation statements)
references
References 34 publications
5
88
1
1
Order By: Relevance
“…The calculated fractional hepatic insulin extraction reported in the present study is higher than the estimated ϳ50% in the dog (2,4) but consistent with values reported in most human studies (5)(6)(7)44). In particular, based on a similar hepatic-vein sampling technique, hepatic first-pass extraction of insulin has been estimated as 70 -85% by different groups (7,45,46).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The calculated fractional hepatic insulin extraction reported in the present study is higher than the estimated ϳ50% in the dog (2,4) but consistent with values reported in most human studies (5)(6)(7)44). In particular, based on a similar hepatic-vein sampling technique, hepatic first-pass extraction of insulin has been estimated as 70 -85% by different groups (7,45,46).…”
Section: Discussionsupporting
confidence: 90%
“…Five nondiabetic subjects (two men and three women, mean age 32 years [range 25 F ollowing insulin secretion, the first organ of impact is the liver, where a proportion of secreted insulin is cleared through a receptormediated process (1)(2)(3). The proportion of insulin cleared has been estimated as ϳ50% in dogs (2,4) and ϳ40 -80% in humans (5)(6)(7)(8). Insulin is secreted in discrete secretory bursts occurring approximately every 4 min (9,10).…”
mentioning
confidence: 99%
“…Although it was possible that a small oral glucose load caused a bigger error than a larger one, 0.2 g/kg glucose was administered orally to prevent a temporary increase in plasma glucose after oral glucose load. It has been reported that absorption of oral loading glucose (12.5 25 g), which is a similar amount to the glucose load in the present study, from the gut is completed within 2 h in healthy subjects [27] and dogs [28]. The rate of absorption of the oral glucose load in NIDDM subjects was shown to be comparable to that in normal subjects [29].…”
Section: Discussionsupporting
confidence: 78%
“…However, high serum concentrations of free insulin are to be anticipated as most diabetic subjects were receiving an insulin infusion of 100 mU/min, and some even of 200 mU/min. Thus the insulin dose administered by the glucose controlled insulin infusion system for assimilation of 50g of glucose was considerably greater than the 6.8_ 1.4 U (SEM) of insulin released by healthy man after ingestion of the same glucose load [37]. This implies that the induced over-insulinization of the diabetic patients might have reduced any expected effects of the weaker counter-regulatory hormones, glucagon and cortisol on glucose assimilation.…”
Section: Discussionmentioning
confidence: 91%